2021
DOI: 10.47430/ujmr.2161.004
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 (COVID-19): A Cross-Sectional Survey of the Knowledge, Attitudes, Practices (KAP) and Misconceptions in the General Population of Katsina State, Nigeria

Abstract: Over six million cases of Coronavirus Disease 2019 (COVID-19) were reported globally by the second quarter of 2020. This study assessed the COVID-19 related knowledge, attitudes, practices and misconceptions in Katsina state, Nigeria. The study is across-sectional survey of 722 respondents using an electronic questionnaire through the WhatsApp media platform. One thousand five hundred questionnaires were sent to the general public with a response rate of 48%. Among the respondents, 60% were men, and 56% held b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…In addition, this study revealed that the proportion of respondents with a high level of knowledge was higher among people with a formal education (who had attained at least a primary level), compared to those without a formal education. This was in agreement with the findings of Isah et al in Nigeria, who reported that higher levels of education are associated with high knowledge of COVID-19 and its prevention guidelines (29). The present study reported that most of the respondents strongly agreed that masks can help prevent COVID-19.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, this study revealed that the proportion of respondents with a high level of knowledge was higher among people with a formal education (who had attained at least a primary level), compared to those without a formal education. This was in agreement with the findings of Isah et al in Nigeria, who reported that higher levels of education are associated with high knowledge of COVID-19 and its prevention guidelines (29). The present study reported that most of the respondents strongly agreed that masks can help prevent COVID-19.…”
Section: Discussionsupporting
confidence: 93%
“…Then, previous research was found by (Fiolina & Elizabeth, 2023) and (Alvian, 2021) it was found that service quality has a positive and significant influence on customer satisfaction. However, it is different from the results of previous research (Choiriah & Liana, 2019) and (Ibrahim & Thawil, 2019) found that has no significant influence on service quality or consumer satisfaction. Furthermore, Satisfaction means the feeling of happiness or disappointment that is felt by someone when they have just compared the impression of a product until their expectations are met.…”
Section: Introductioncontrasting
confidence: 99%
“…Several surveys on adherence to masking, social distancing, and hand hygiene have been conducted in multiple countries, some of which are nationally representative [64]. Studies from Nigeria, Malawi, Ethiopia, Ghana, Kenya, and the DRC showed that although most participants had a good knowledge about COVID-19 transmission modes and prevention mechanisms that were consistent over place and time, there were gaps in the practices that prevent COVID-19 [65][66][67][68][69]. Studies further determined that individuals' age, sex, educational status, occupation, and income level were associated with COVID-19 related practices [65,67,70,71].…”
Section: Early Government Measures and Messagingmentioning
confidence: 99%
“…Studies from Nigeria, Malawi, Ethiopia, Ghana, Kenya, and the DRC showed that although most participants had a good knowledge about COVID-19 transmission modes and prevention mechanisms that were consistent over place and time, there were gaps in the practices that prevent COVID-19 [65][66][67][68][69]. Studies further determined that individuals' age, sex, educational status, occupation, and income level were associated with COVID-19 related practices [65,67,70,71]. From these studies, it can be concluded that awareness and (non)adherence to NPIs does not explain low reported cases.…”
Section: Early Government Measures and Messagingmentioning
confidence: 99%